2018
DOI: 10.1080/21513732.2018.1489306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in ecosystem service delivery – a historical perspective on catchment landscapes

Abstract: Although the relationships between habitats and ecosystem services (ESs) have been acknowledged, investigating spatio-temporal change in these has received far less attention. This study assesses the influence of habitat changes on ES delivery across space and time, based on two time points some 60 years apart, 1946 and 2009. A 1946 aerial photo coverage of two catchments in Scotland was used to construct digital photo mosaics which were then visually interpreted and digitised to derive historic habitat maps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This specialisation of production is a factor which contributed to shaping the bundles in the study region. In a study of historical change in the agricultural landscape in the Scottish Borders, Ncube et al (2018) similarly showed that changes in ecosystem services between time periods 60 years apart reflected changes in agriculture policy leading to concurrent switches in service provision between competing regulating and provisioning services (Ncube et al (2018)).…”
Section: Drivers For Ecosystem Services Bundlesmentioning
confidence: 99%
“…This specialisation of production is a factor which contributed to shaping the bundles in the study region. In a study of historical change in the agricultural landscape in the Scottish Borders, Ncube et al (2018) similarly showed that changes in ecosystem services between time periods 60 years apart reflected changes in agriculture policy leading to concurrent switches in service provision between competing regulating and provisioning services (Ncube et al (2018)).…”
Section: Drivers For Ecosystem Services Bundlesmentioning
confidence: 99%
“…Relatively few other studies have examined the temporal dynamics of ES provision ; examples include Renard et al (2015) in Ncube et al (2018) in southern Scotland. In the former study, spanning 35 years, Renard et al (2015) found that provision of most ES increased through time, although the rate of increase varied spatially.…”
Section: Discussionmentioning
confidence: 99%
“…Soils on steeper hillsides are typically freely‐draining brown soils but towards the base of the hillslopes and in the west soils comprise sequences of gleyed clays and peats, or alluvial deposits closer to the river (Soil Survey of Scotland Staff, 1970). Upstream of Peebles (Figure 1) the catchment is entirely rural and agriculture is dominated by sheep grazing on improved and semi‐improved grassland (Ncube, Spray, & Geddes, 2018), with plantation forestry above 300 m OD in much of the western catchment, covering up to 70% of some smaller catchments. The catchment has undergone extensive human‐induced changes over the last 500 years including deforestation, land drainage, river straightening and afforestation (Harrison, 2012).…”
Section: Methodsmentioning
confidence: 99%